Levofloxacin in everyday ophthalmic practice – review - Post, Michał; Okruszko, Anna; Szaflik, Jacek P. (Klinika Oczna / Acta Ophthalmologica Polonica, 2021)
Fluoroquinolones are among the most widely used antibiotics in ophthalmology. Based on the example of levofloxacin, the authors review the literature on the applications of fluoroquinolones in everyday ophthalmic practice. The analysis focuses on evaluating the role of levofloxacin in the treatment of the most common infections and perioperative prophylaxis, antibiotic resistance to fluoroquinolones, and safety of this group of drugs.